Inactive Gingipains from P. gingivalis Selectively Skews T Cells toward a Th17 Phenotype in an IL-6 Dependent Manner - Glowczyk, Izabela; Wong, Alicia; Potempa, Barbara; Babyak, Olena; Lech, Maciej; Lamont, Richard J.; Potempa, Jan; Koziel, Joanna (Frontiers in Cellular and Infection Microbiology, 2017)
Gingipain cysteine proteases are considered key virulence factors of Porphyromonas gingivalis. They significantly influence antibacterial and homeostatic functions of macrophages, neutrophils, the complement system, and cytokine networks. Recent data indicate the role of P. gingivalis in T cell differentiation; however, the involvement of gingipains in this process remains elusive. Therefore, the aim of this study was to investigate the contribution of danger signals triggered by the gingipains on the generation of Th17 cells, which play a key role in protection against bacterial diseases but may cause chronic inflammation and bone resorption. To this end we compared the effects of the wild-type strain of P. gingivalis (W83) with its isogenic mutant devoid of gingipain activity (ΔKΔRAB), and bacterial cells pretreated with a highly-specific inhibitor of gingipains activity (KYTs). Antigen presenting cells (APCs), both professional (dendritic cells), and non-professional (gingival keratinocytes), exposed to viable bacteria expressed high amounts of cytokines (IL-6, IL-21, IL-23). These cytokines are reported to either stimulate or balance the Th17-dependent immune response. Surprisingly, cells infected with P. gingivalis devoid of gingipain activity showed increased levels of all tested cytokines compared to bacteria with fully active enzymes. The effect was dependent on both the reduction of cytokine proteolysis and the lack of cross-talk with other bacterial virulence factors, including LPS and fimbriae that induce de novo synthesis of cytokines. The profile of lymphocyte T differentiation from naive T cells showed enhanced generation of Th17 in response to bacteria with inactive gingipains. Moreover, we found that gingipain-dependent induction of Th17 cells was highly specific, since other T cell-subsets remained unchanged. Finally, inhibition of IL-6 signaling in dendritic cells led to a significant depletion of the Th17 population. Cumulatively, this study revealed a previously undisclosed role of gingipain activity in the process of Th17 differentiation reliant on blocking signaling through IL-6. Since inactivation of gingipains accelerates the skewing of T cells toward Th17 cells, which are detrimental in periodontitis, IL-6 signaling may serve as an attractive target for treatment of the disease.